ΝΙΚΟΣ ΖΑΚΟΠΟΥΛΟΣ: ΕΝΑΣ ΙΑΤΡΟΣ ΠΟΥ ΕΓΡΑΦΕ ΘΕΑΤΡΙΚΑ ΕΡΓΑ Ή ΕΝΑΣ ΘΕΑΤΡΙΚΟΣ ΣΥΓΓΡΑΦΕΑΣ ΠΟΥ ΕΓΡΑΦΕ ΙΑΤΡΙΚΑ ΣΥΓΓΡΑΜΜΑΤΑ; [NIKOS ZAKOPOULOS: A DOCTOR WHO WROTE PLAYS OR A PLAYWRIGHT WHO WROTE MEDICAL BOOKS?] - Kyriakou, Konstantinos (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
Nikos Zakopoulos (1917-1997) can be considered one of the most successful playwrights of his time, as almost all the plays he wrote, individually or in collaboration with other playwrights, were presented on stage, with several of them awarded at the state competitions. In fact, there were theatrical seasons, during which two and/or three of his plays were performed simultaneously. However, after his death, his works were ‘banished’ from the repertoire of Greek troupes. Nikos Zakopoulos experimented in almost all theatrical genres; he dabbled in drama and satire, moved from allegory to symbolic and historical drama, and experimented in poetic theater as well as the Theater of the Absurd. In his works he deals with the crushing and exhaustion of man under the consequences of technocratic omnipotence and new forms of relationships, created by the hypertrophic and thoughtless development of modern forms of life (advertising, confusion, violence, greed for profit, non-human states, consumerism, etc.). All conflicts focus on the discord and distress that arise in the struggles between technological society and the biological and psychological needs of people.